2008
DOI: 10.1016/j.molcel.2008.05.016
|View full text |Cite
|
Sign up to set email alerts
|

A PP4-Phosphatase Complex Dephosphorylates γ-H2AX Generated during DNA Replication

Abstract: Summary The histone H2A variant H2AX is rapidly phosphorylated in response to DNA double-stranded breaks to produce γ-H2AX. γ-H2AX stabilizes cell cycle checkpoint proteins and DNA repair factors at the break site. We previously found that the protein phosphatase PP2A is required to resolve γ-H2AX foci and complete DNA repair after exogenous DNA damage. Here we describe a three-protein PP4 phosphatase complex in mammalian cells, containing PP4C, PP4R2 and PP4R3β, that specifically dephosphorylates ATR-mediated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
249
1
7

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 220 publications
(266 citation statements)
references
References 47 publications
9
249
1
7
Order By: Relevance
“…The time course of H2AX phosphorylation in TPX2-depleted cells differs from those observed when specific ␥-H2AX protein phosphatases are depleted in which cases prolonged ␥-H2AX signals are observed (77)(78)(79)(80)(81)(82). In contrast, TPX2-depleted cells silence their elevated ␥-H2AX signals with the same time course as control cells (Fig.…”
Section: Discussionmentioning
confidence: 78%
“…The time course of H2AX phosphorylation in TPX2-depleted cells differs from those observed when specific ␥-H2AX protein phosphatases are depleted in which cases prolonged ␥-H2AX signals are observed (77)(78)(79)(80)(81)(82). In contrast, TPX2-depleted cells silence their elevated ␥-H2AX signals with the same time course as control cells (Fig.…”
Section: Discussionmentioning
confidence: 78%
“…Since cisplatin is a replication-dependent DNA-damaging agent [8], this suggests that PP4 is involved in DNA damage signaling and/or repair. Indeed, we recently found that PP4C dephosphorylates γ-H2AX generated during DNA replication [9], while PP2A dephosphorylates γ-H2AX generated in response to exogenous DNA damaging agents [10].…”
Section: Dear Editormentioning
confidence: 99%
“…Resistance may be attributed to several factors, including enhanced DNA repair, tolerance to platinum-induced DNA damage, and alterations in signal transduction pathways [8]. We recently demonstrated that PP4C is the phosphatase that dephosphorylates γ-H2AX generated during DNA replication [9]. High levels of PP4C in cells may dephosphorylate replication block-associated γ-H2AX, promote DNA replication regardless of replication block, escape cisplatin-induced apoptosis, and accumulate DNA mutations, which further predispose cells to genomic instability.…”
Section: Dear Editormentioning
confidence: 99%
“…To date, the S. cerevisiae Ser/Thr phosphatases Ptc2 and Ptc3, as well as the protein phosphatase 4 (PP4)-like protein phosphatase Pph3, have been found to be important for checkpoint recovery after a single DSB (17,18). Furthermore, Pph3/PP4 is required for ␥H2A dephosphorylation, which contributes to recovery from a DSB-induced checkpoint (4,17,25). Finally, Pph3 and Ptc2 have been implicated in Rad53 dephosphorylation and hence deactivation during recovery from MMS exposure (26,32).…”
mentioning
confidence: 99%